2014
DOI: 10.1016/j.seizure.2014.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Left dominance of EEG abnormalities in patients with transient global amnesia

Abstract: In this largest consecutive EEG study at one center, the proportion of patients with TGA in whom epileptiform discharges were demonstrated within days of the episode of TGA was significantly higher than in the previous literature. EEG abnormalities such as spikes or sharp waves spontaneously disappeared in almost half of cases over one-year of follow-up. There was a clear left dominance of EEG abnormalities in patients with TGA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 30 publications
5
24
0
Order By: Relevance
“…In addition, the voxel-based whole brain analysis also revealed cerebral hypoperfusion in the left inferior temporal and superior parietal cortex and in the left precuneus. This finding of left lateralization is in line with other studies that reported some left dominance of functional abnormalities confirmed via EEG, perfusion MRI or SPECT abnormalities [ 27 , 28 , 54 , 55 ]. Considering that visual reading of SPECT images and DWI lesions are not related to left dominance ( Table 1 ), there may be some discrepancies from the findings of the voxel-based whole brain analysis or the quantitative ECD uptake.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, the voxel-based whole brain analysis also revealed cerebral hypoperfusion in the left inferior temporal and superior parietal cortex and in the left precuneus. This finding of left lateralization is in line with other studies that reported some left dominance of functional abnormalities confirmed via EEG, perfusion MRI or SPECT abnormalities [ 27 , 28 , 54 , 55 ]. Considering that visual reading of SPECT images and DWI lesions are not related to left dominance ( Table 1 ), there may be some discrepancies from the findings of the voxel-based whole brain analysis or the quantitative ECD uptake.…”
Section: Discussionsupporting
confidence: 92%
“…One possible explanation is that the effect of left cerebral hypoperfusion contributing to amnestic events in TGA patients could be greater or persist longer than that of the right side, although bilateral cerebral hypoperfusion may occur at the initial stage of TGA. We speculated that this finding regarding left laterality could be closely linked to a previous study reported by our team, which revealed significant left predominance of EEG abnormalities [ 54 ].…”
Section: Discussionsupporting
confidence: 79%
“…These findings are compatible with our previous study using VBM, which also found volume reductions in the left hippocampus only. This left lateralization is consistent with other previous studies using EEG and SPECT (Chung et al., ; Jang et al., ; Kwon et al., ). Kim et al.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are compatible with our previous study using VBM, which also found volume reductions in the left hippocampus only. This left lateralization is consistent with other previous studies using EEG and SPECT (Chung et al, 2009;Jang et al, 2015;Kwon et al, 2014). Kim et al analyzed EEG abnormalities in patients with TGA; epileptiform discharge, or focal slowing, was detected in the left hemisphere only (54.3%) or in both hemispheres (28.6%), but not in the right hemisphere only (0%) .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation